PENGARUH INDIKASI KECURANGAN TERHADAP KECURANGAN LAPORAN KEUANGAN DALAM PERSPEKTIF FRAUD PENTAGON - DIRVI SURYA ABBAS; ARRY EKSANDY; MOHAMAD ZULMAN HAKIM; ISMAIL SYAM (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Effects of Fraud Indications on Fraudulent Financial Statements in Pentagon Fraud Perspectives on Property and Real Estate Companies Listed on the Indonesia Stock Exchange in the 2016-2018 Period. The time period of the study is 3 years, the period 20162018. The F-Score is used to determine financial statement fraud. The population of this study includes the Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange in the 2016-2018 period totaling 19 companies. The sampling technique uses purposive sampling technique. The results showed that in terms of financial stability, the nature of the industry, the number of photos of changes in directors had no effect on financial statement fraud. However, changes in the auditor’s influence on financial statement fraud